Radon Exposure and Cancer Risk: Assessing Genetic and Protein Markers in Affected Populations - Yerlan Kashkinbayev; Baglan Kazhiyakhmetova; Nursulu Altaeva; Meirat Bakhtin; Pavel Tarlykov; Elena Saifulina; Moldir Aumalikova; Danara Ibrayeva; Aidos Bolatov (Biology)
Radon is an inert gas produced by the radioactive decay of uranium-238, commonly found in the environment. Radon and its decay products are the main sources of human exposure to radiation from natural sources. When inhaled, radon’s alpha particles impact lung tissue, potentially causing lung cancer by damaging DNA and altering oxidative processes. This review article addresses the need for a deeper understanding of the genetic and molecular changes associated with radon-induced lung cancer, aiming to clarify key genetic mutations and protein markers linked to carcinogenesis. Particular attention in recent studies has been given to mutations in tumor suppressor genes (RASSF1, TP53), oncogenes (KRAS, EGFR), and changes in the expression levels of protein biomarkers associated with inflammation, stress, and apoptosis. Identifying these markers is critical for developing effective screening methods for radon-induced lung cancer, enabling timely identification of high-risk patients and supporting effective preventive strategies. Summarizing current genetic and protein biomarkers, this review highlights the importance of a comprehensive approach to studying radon-induced carcinogenesis. Understanding these molecular mechanisms could ultimately improve early diagnostic methods and enhance therapy for cancers associated with radon exposure.